Caring systems: making relational, gameful self-care technologies for mental health - Spors, Alexa Velvet (2022)
Mental-health-focused self-care technologies (SCTs), as tools to look after oneself, receive great interest from human computer interaction and beyond. Sitting somewhere between medical intervention, preventive healthcare and tools for personal experience or expression, SCTs are seen as vehicles that can deliver personalised, 24/7 care. As proliferating everyday technologies, SCTs draw inspiration from a plethora of fields and paradigms—including games and games studies to augment and extend SCTs through game-informed, gameful features. To be able to provide self-care for mental health, SCTs must necessarily communicate and embody understandings of the concepts they feature or seek to address. This thesis argues that current SCTs conceptualise self-care for mental health as a linear, individualistic pursuit of wellness. Heavily informed by medicalisation, this dominant understanding leads to the construction of a normative, reductive design frame. Instead of a holistic engagement with mental health, as a multi-faceted, experiential—and often complicated—quality in someone’s life, self-care for mental health is often flattened into a universal “one-size-fits-most” approach. This reductive approach also extends to games as an inspirational source for SCTs. Instead of conceptualising and learning from games as an existing part of people’s self-care practise in holistic terms, games are often only operationalised to enhance existing normative approaches.